A case study of developing a Paralympic shooting jacket for disabled athletes - Hobbs-Murphy, K.; Morris, K.; Park, J. (Clothing and Textiles Research Journal, 2024)
Disabled athletes participate in sports at elite levels; however, industry product and academic research regarding adaptive sportswear is lacking. Limited availability of sportswear can be a barrier to participation in athletics for disabled people, particularly athletes with mobility differences. This study therefore aimed to enhance the sportswear design process in a single-case study of a Paralympic shooting athlete who participated in the 2020 Paralympic games. Qualitative and anthropometric data were collected via a high-communication, five-step design process. The researchers explored 3D apparel design technologies in tandem with physical prototyping methods to understand benefits and challenges of said tools in adaptive sportswear development. Key findings of this work include understanding of disabled athletes` needs, design considerations for adaptive sportswear development, and found benefits and challenges of technology use. The knowledge acquired in this case study offers valuable contributions for researchers and manufacturers that can advance sportswear design for all disabled athletes.